Factors Influencing Turnover Intention among Nurses and Midwives in Ghana - Angelina Boatemaa Boateng; Douglas Aninng Opoku; Nana Kwame Ayisi-Boateng; Alhassan Sulemana; Aliyu Mohammed; Joseph Osarfo; Jonathan N. Hogarh (Nursing Research and Practice)
Background. Nurse turnover intention, defined as a measure of nurses’ desire to leave their positions, is a global public health issue with a grave impact on the healthcare workforce. However, literature on it is limited in sub-Saharan Africa, an at-risk region. This study aimed to determine the predictors of turnover intention among nursing staff at a tertiary hospital in Kumasi, Ghana. Methods. This was an institution-basedcross-sectional study conducted among 226 randomly selected nurses and midwives working at a tertiary healthcare center in Kumasi, Ghana. Data were collected by using a structured questionnaire. Significant predictors of turnover intention were analyzed by using multivariate logistic regression analysis. Adjusted odds ratio (AOR) with a 95% confidence interval (CI) and p value <0.05 was used. Results. The prevalence of turnover intention among study participants was 87.2% (197/226). About two-thirds (61.5%, 139/226) of the participants were exposed to a high level of workplace hazards. Management support (AOR = 3.09, 95% CI = 1.09–8.75), salary (AOR = 0.07, 95% CI = 0.01–0.46), inadequate number of staff on duty per shift (AOR = 3.36, 95% CI = 1.08–10.47) and participants’ rank (AOR = 6.81, 95% CI = 1.18–39.16) were significantly associated with turnover intention. Conclusion. Overall, the turnover intention was high. Hence, there is a need for policymakers, health administrators, and nurse managers to implement strategies such as increasing staff strength, providing adequate support, incentives, and other forms of motivation for nurses and midwives to help reduce the rate of turnover intention.